أثر برنامج قائم على مدخل العلم والتكنولوجيا والمجتمع STS في تنمية ممارسات النظافة الشخصية والوقاية من الأمراض والأخطار لأطفال الروضة - شعبان، زينب شعبان محمد; محمد، مديحة مصطفى علي Mohammed, Madihah Mustafa Ali; نصر، محمود أحمد محمود; العباسي، أشرف عبدالسلام (جامعة بني سويف - كلية التربية للطفولة المبكرة, 2021)
هدف البحث الحالي إلى التعرف على أثر برنامج قائم على مدخل العلم والتكنولوجيا والمجتمع (STS) في تنمية بعض الممارسات الصحية المتمثلة في النظافة الشخصية وكذلك الوقاية من الأمراض والأخطار لتحقيق هدف البحث استخدمت الباحثة المنهج شبه التجريبي ذو المجموعتين (المجموعة التجريبية، المجموعة الضابطة) حيث تكونت مجموعة البحث من (٦٠) طفلا وطفلة من أطفال المستوى الثاني برياض الأطفال بروضة الزهور بمدرسة الصفا والمروة بمدينة بني سويف الجديدة حيث تم تقسيمها إلى مجموعتين إحداهما تجريبية مكونة من (٣٠) طفلا وطفلة، وتم تطبيق أنشطة البرنامج عليها والأخرى ضابطة مكونة من (٣٠) طفلا وطفلة لم تتعرض لأنشطة البرنامج وتمثلت مواد وأدوات البحث في أنشطة قائمة على مدخل العلم والتكنولوجيا والمجتمع (STS) (إعداد الباحثة) ومقياس الممارسات الصحية المصور (إعداد الباحثة)، وأظهرت نتائج البحث وجود فرق دال إحصائيا عند مستوى دلالة (0.01) بين متوسطي درجات المجموعة التجريبية ودرجات المجموعة الضابطة في التطبيق البعدي لاختبار الممارسات الصحية لصالح المجموعة التجريبية. وفي ضوء هذه النتائج قدمت الباحثة بعض المقترحات والتوصيات.
The aim of the current research is to identify the effect of a program based on science, technology and society approach (STS) on developing some healthy practices represented in personal hygiene and prevention of diseases and dangers, To achieve goal of the research, the researcher used The two-group quasi-experimental approach (experimental group, control group) where The research group consisted of (60) children from the second level of kindergarten at Al Zuhour Kindergarten in Al Safa and Marwa School at new Beni- suef city. It was divided into two groups, one of them is experimental consisting of (30) children were exposed to the activities of the program, and the other is a control group consisting of (30) children who had not been exposed to the activities of the program. The research materials and tools were used to apply the program are activities based on the science, technology and society approach (STS) (researcher preparation) and the illustrated healthy practices scale (researcher preparation). The results of the research showed a statistically significant difference at the level of significance (0.01) between the mean scores of the experimental group and the mean scores of the control group in the post application of testing health practices in favor of the experimental group. In light of these results, the researcher presented some suggestions and recommendations.
Keywords: الثقافة الصحية -- المنظمات التربوية -- العادات الغذائية -- الأنشطة البدنية -- أطفال الروضة